A Novel Mitochondrial DNA 8597T>C Mutation of Leigh Syndrome: Report of One Case - Jeng-Dau Tsai; Chin-San Liu; Teng-Fu Tsao; Ji-Nan Sheu (Elsevier, 2012)
Leigh syndrome is an early-onset progressive neurodegenerative disorder with a characteristic neuropathology consisting of focal, bilateral lesions in one or more areas of the central nervous system. The brain images of Leigh syndrome are characterized by markedly symmetrical involvement, most frequently of the putamen. We report a 2-year-old girl with Leigh syndrome manifested as acute onset of altered level of consciousness. Brain magnetic resonance images showed abnormal signal intensity over the bilateral basal ganglia and cerebellar dentate nuclei. Despite normal biochemical studies, in particular serum lactate levels, magnetic resonance spectroscopy demonstrated a downward doublet lactate peak. The diagnosis of Leigh syndrome was subsequently confirmed by genetic study which showed a novel mutation at 8597T>C of the mitochondrial ATPase6 gene.